Change learn to love it learn to lead it - Gerver, Richard (London Portfolio Penguin, 2013)
This book will give you all you need to understand change, to adapt to change, and to inspire others to do the same. The pace of change is greater than ever. We all face new challenges every day in our jobs and in our personal lives. Those who can handle change are the most fulfilled. Those who fear change will find it hardest to thrive. As a head teacher, Richard Gerver famously transformed a failing school into one of the most acclaimed learning environments in the world?in just two years. He inspired staff and teachers to reach their full potential. As a hugely popular speaker and author, he now helps individuals and companies to embrace change. This book is his powerful personal reflection on change. Full of wisdom and practical insights, it will help you in any situation you face. Whether you are leading a company through change or looking for a new direction in life, let Richard Gerver be your guide.
Includes
Keywords: Change